Most consumed ligneous forages in ruminant breeding on natural pasture in north of Benin - SIDI, Habirou; GUEDOU, Aimé; AWOHOUEDJI, Doha Yétongnon G.; BABATOUNDE, SÉVÉRIN (My University, 2016)
There are rainfall dependent and rainfall less dependent forages. The present study, conducted in districts of Nikki, Kalalé, Ségbana and Gogounou located in north-east of Benin republic, deals with less dependent on rainfall ligneous’ forage which are important forages resources available and accessible throughout the year. The methodological approaches used are: participatory diagnosis. The useful timbers which leaves are used in ruminant feeding are Pterocarpus erinaceus, Afzelia africana and Khaya senegalensis. Facing the regression of those palatable species due to climate change and overexploitation, twenty-six other woody species previously without any interest to bovine nutrition are increasingly used in drought. However, the contribution of those 26 species in ruminants’ feeding could be limited by the availability, accessibility and palatability.
Keywords: Endogenous; perception; Ligneous’ forage; Ruminants’ nutrition; Benin